The Influence of Interpersonal Communication on Emotional Regulation of Broken Home Students with Suicide Ideation - NAYYA DESRIAL MARSANDA (Causalita, 2025)
This study aims to see the effect of interpersonal communication on emotional regulation in Broken Home students who have suicidal ideas. The approach used is quantitative by involving 98 students as respondents. The instruments in this study were collected using an interpersonal communication scale compiled based on DeVito's theory (1997) which was adopted from Aprillia's research (2023). And the emotional regulation instrument in this study adopted a scale compiled based on aspects of emotional regulation according to Gross, which was developed by Yunita and Naqiyah (2023). Data were collected through a gform that measures interpersonal communication variables and emotional regulation, then analyzed using simple linear regression. The results showed a significant effect of interpersonal communication on emotional regulation (p <0.05), with a regression coefficient of 0.554. The results of the study illustrate that good interpersonal skills will improve students' emotional management abilities, which emotional regulation can reduce the desire to commit suicide and reduce the suicide rate itself.